MENINGKATKAN KESADARAN MAYARAKAT PENTINGNYA LINGKUNGAN YANG BERSIH DI DESA SIMARTUGAN - Reaful Samuel Sitorus; Ronita Haulian Simamora; Deo Kartiko Ambarita; Welmar Olfan basten Barat (Abdi Jurnal Publikasi, 2023)
Simartugan Village is one of the villages in Pegagan Hilir District, Dairi Regency, North Sumatra Province. This village is inhabited by 525 families with a total population of 2029 people. Simartugan village consists of 6 hamlets, namely, Simartugan I, Simartugan Julu I, Simartugan Julu II, Kuta Great, Tanggarube, Jumambalno, where agriculture is the main source of livelihood for its inhabitants. A good and healthy environment is very important in supporting human survival. The environment is everything that is around us, whether alive or not, such as air, water, soil and everything on it such as plants, animals, microorganisms (Suanta, 2016). This community service is carried out with a social approach, where this is more easily applied in a society that is more prominent in cultural, kinship and environmental ties. In this way, the social capital approach allows for reciprocal ties with local communities. Social capital as social glue in these communities will largely be determined as an accumulation of various types of social, psychological, cultural aspects that influence cooperative behavior. With the description of social capital as above, it is believed that such an approach can be used as a means to socialize the importance of clean environmental conditions to the community. The results obtained show that the number of people attending to carry out mutual cooperation activities is very low where this is influenced by several factors, namely: Lack of public awareness of the importance of a clean environment, The economic conditions of the community where the main livelihood of the Simartugan village community is farming. The community prefers to work in the fields rather than having to participate in mutual cooperation activities. When mutual cooperation activities coincide with the harvest season in Simartugan village, this makes the community prefer to work and harvest on the land they own. Lack of communication between the hamlet head and the community local.